2016
DOI: 10.1016/j.ajog.2016.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of human papillomavirus (HPV) 16 and 18 vaccination on prevalent infections and rates of cervical lesions after excisional treatment

Abstract: BACKGROUNDHuman papillomavirus (HPV) vaccines prevent HPV infection and cervical precancers. The impact of vaccinating women with a current infection or after treatment for an HPV-associated lesion is not fully understood.OBJECTIVESTo determine whether HPV-16/18 vaccination influences the outcome of infections present at vaccination and the rate of infection and disease after treatment of lesions.STUDY DESIGNWe included 1711 women (18–25 years) with carcinogenic human papillomavirus infection and 311 women of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 17 publications
4
105
0
1
Order By: Relevance
“…While the HPV vaccine efficacy in ano-genital HPV prevention is well established, its utility in treatment is viewed by many with skepticism. The cell biology of how neutralizing antibodies prevent infection [27] has been established but it does not include a pathway that would predict eradication of established infection, particularly high-risk HPV, and clinical studies in cervical infection [28,29] and genital warts [30] confirm as much. For several decades, Bonagura et al have investigated the cellular humoral response in RRP [31].…”
Section: Plos Onementioning
confidence: 99%
“…While the HPV vaccine efficacy in ano-genital HPV prevention is well established, its utility in treatment is viewed by many with skepticism. The cell biology of how neutralizing antibodies prevent infection [27] has been established but it does not include a pathway that would predict eradication of established infection, particularly high-risk HPV, and clinical studies in cervical infection [28,29] and genital warts [30] confirm as much. For several decades, Bonagura et al have investigated the cellular humoral response in RRP [31].…”
Section: Plos Onementioning
confidence: 99%
“…For these HPV16/18 infections, in the cohort of women with HPV infection but without precancer, the efficacy of clearance was 5.4%, with progression to CIN1 seen for 15.5%, and to CIN2, for 0.3%. Moreover, after the loop electrosurgical excision, the vaccination had no significant effects on HPV16/18 infections and/or HPV16/18-associated cytological and histological lesions (127).…”
Section: Hpv Prophylactic Vaccines Used As Therapeutic Vaccinesmentioning
confidence: 90%
“…[20] Studies have found that the vaccine strongly protects against HPV acquisition,[21,22] but does not impact HPV clearance or disease regression;[23] and that most ICCs do not develop for at least one decade after HPV acquisition. [24,25] The vaccine was approved in 2006, seven years prior to our end of follow-up.…”
Section: Discussionmentioning
confidence: 99%